Design of the "Hygroscopic Clothing" in Medical Protective Clothing (Journal of Fiber Bioengineering and Informatics, 2023)
To solve the current lack of thermal and humidity comfort in medical protective clothing for workers in high-risk environments, this paper seeks to adopt moisture-absorbing materials in the design of work clothes for medical staff, thus presenting an innovative design framework for hygroscopic workwear. This paper uses hospital staff in high-risk environment, such as nurses who operate within hospital hot zones and community service personnel, as research subjects. Their activities were recorded and subsequently analyzed Then, the MET values of these actions were discovered and listed. After calculation, the average medium-high-intensity work MET value was ≈5.8, and the medium-low-intensity MET value was ≈2.8, with the corresponding speed of 6.3 km/h and 2.8 km/h, respectively. These two speeds were the references for human motion experiments.In the human motion experiment, the objects wore medical protective clothing, the ambient temperature was set to 26-28°n, and the motion status was determined to be 2.8 km/h: 5 min-6.3 km/h: 25 min-2.8 km/h: 10 min. The filtering paper method was employed to measure the regional body sweat. Then, the regional body sweat map was obtained. According to the results, the structural scheme for hygroscopic workwear was proposed to further promote the research process of the hygroscopic workwear.In the human body wearing verification experiment, the experimental group was the subjects wearing hygroscopic clothes, and the control group was the subjects wearing pure cotton clothing. In the process of exercise, the hygroscopic performance of the work clothes was compared by the changes of internal environment humidity and the feelings of subjects. Through data analysis, compared with pure cotton upper and lower garment, the hygroscopic work clothes can effectively maintain the comfortable balance of internal environment humidity.
Keywords: Thermal and Humidity Comfort; Clothing Structure; Medical Protective Clothing; Work Intensity; Sweating Amounts.